Development of the Coordination Course (C-Course) for Disaster Health Management (DHM) in the Asean - Shuich Ikeda; Kriangsak Pintatham; Tsukasa Katsube; Taro Kita; Mika Aono (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: Development of a standard curriculum for the Coordination course (C-Course) was initiated during the ARCH extension phase, 2019-2021. The objective of this article is to clarify important perspectives for application of the standard curriculum of the C-Course to each AMS and to be shared them especially for in-country training course developers. Methods: The C-Course must include contents on international and regional guidelines/procedures for EMT operations as well as domestic policies/rules/regulations on disaster management and inter-governmental coordination mechanisms for disaster response. The standard curriculum and teaching materials were developed through the following three phase process: Phase 1. Development of proto-type program and session plan; Phase 2. Conduct of Trial C-Course in Japan; Phase 3. Application of C-Course to Malaysia. Results: Through the above three phase process, the standard program and session plan for the C-Course were developed with the application of the C-Course in the Malaysian context, dividing it into two parts which are the pre-learning online lectures for general theories and international/regional guidelines on EMT coordination and the in-person workshop with abundant scenario-based group discussions and group works. Discussion: Development process for standard curriculum for the Coordination course (C-Course) was almost completed. Conclusion: The C-course has to be further tailored to suit other AMS’s situations so that all the AMS could conduct their own in-country C-courses.